Asuhan Kebidanan Pada Ibu Hamil Di PMB Husnel Hayati Wilayah Kerja Puskesmas Salo Tahun 2022 - Zulia, Irma; Dhilon, Dhini Anggraini (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Data World Health Organization (WHO) in 2019 Maternal Mortality Rate (AKI) is a maternal mortality rate caused by the process of pregnancy, childbirth, and after delivery which is used as an indicator of the degree of female health. One way to reduce the battery is to apply midwifery care to pregnant women. The purpose of this study was to determine the midwifery care of pregnant women in PMB Husnel Hayati working area of ??the Salo Health Center in 2022. This study used a descriptive observational research design with a case study approach. The research subjects in this study were pregnant women in Husnel Hayati. Data was collected by conducting direct interviews with pregnant women, respondents' families and physical examinations and supporting examinations, namely physical examination. On the first day to the fifth day, the management of back pain with massage. Based on the care of labor conducted on Ny. R is found that the patient's back pain is reduced. Conclusion Midwifery care is carried out, effective and can overcome the problem of research subjects. It is hoped that this research can increase more knowledge and skills with increasingly advanced times and improve the quality of midwifery care given to patients directly in comprehensive midwifery care